THE EFFECT OF PRODUCT QUALITY AND BRAND IMAGE ON BUYING INTEREST DECISIONS AT OKI SERBA 8000 BATAM STORES - Hutasoit, Irma Yulianti; Hikmah, Hikmah (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study examines the significant influences of product quality and brand image on purchase intentions at Toko Oki Serba 8000 Batam. Employing a quantitative approach, the research utilizes primary data collected through observations and questionnaires from 204 respondents. Data analysis techniques include multiple regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-tests, and F-tests performed using SPSS Version 26. Findings from the t-test suggest a significant relationship between product quality and buying interest, indicating that buying interest is influenced by product quality to a certain extent. Meanwhile, brand image significantly impacts buying interest. F-test results lead to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha), confirming that purchase intentions at the Oki Serba 8000 store are significantly influenced by both product quality and brand image. This study highlights the critical role of these factors in shaping consumer purchase behavior and offers insights for retailers to enhance marketing strategies focusing on product quality and brand image to boost customer buying interest